Study on the Calculation Method of Active Earth Pressure and Critical Width for Finite Soil Behind the Retaining Wall - Huang, Kan; Liu, Runing; Sun, Yiwei; Li, Linyi; Xie, Yipeng; Peng, Xuejun (Frontiers in Earth Science, 2022)
The method to determine the active earth pressure and critical width for finite soil behind the retaining wall in mountainous area is one of the concerns of geotechnical engineering. In order to study the active earth pressure distribution of the finite soil against the retaining wall and determine the critical width of the boundary between the finite soil and the semi-infinite soil, this study focuses on investigating a retaining wall with finite cohesionless backfill. The shape of the failure surface is assumed to be a cycloid passing through the heel of the wall in the limit equilibrium state. Considering the deflection of soil principal stress induced by wall-soil friction effect, a calculation method of active earth pressure for finite soil is proposed by using arc-shaped small principal stress trajectory, and the rationality of this method is verified. On this basis, a calculation formula of the critical width of finite soil is proposed. The influence of the internal friction angle and the wall-soil friction angle on the critical width of finite soil is examined. The results indicate that the active earth pressure of finite soil presents a nonlinear drum distribution along the height of retaining wall under the failure mode of cycloidal surface. The maximum value of active earth pressure is close to the bottom of the wall. The critical width of finite soil decreases with the increase of internal friction angle, and its variation rate decreases gradually. The critical width of finite soil increases with the increase of wall-soil friction angle, and its variation rate also increases gradually. Under different internal friction angles and wall-soil friction angles, the critical width values of finite soil calculated by the assumption of cycloidal failure surface are smaller than those calculated by Coulomb earth pressure calculation method.